2013
DOI: 10.1002/ajmg.a.36177
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution analysis of copy number variants in adults with simple‐to‐moderate congenital heart disease

Abstract: As patients with congenital heart disease (CHD) increasingly survive to childbearing age, it becomes important to understand the genetic origins of CHD. In children, CHD is frequently caused by chromosomal imbalances. We searched for submicroscopic imbalances in adults with CHD focusing on simple-to-moderate phenotypes, without associated dysmorphic features, a group not previously examined. A total of 100 Han Chinese adults with a diverse range of isolated CHD and 65 ethnically matched controls were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
2
15
0
2
Order By: Relevance
“…Overall Kurahashi et al, 1996;Garcia-Miñaur et al, 2002;Rauch et al, 2005;D'Angelo et al, 2007;Jalali et al, 2008;Fernández et al, 2009;Yu et al, 2011;Verhagen et al, 2012;Zhao et al, 2013;Rump et al, 2014; and this study. * Includes cases of Racedo et al, 2015 who only examined cardiac features of 25 individuals.…”
Section: Central Deletions (B-d C-d)supporting
confidence: 55%
See 2 more Smart Citations
“…Overall Kurahashi et al, 1996;Garcia-Miñaur et al, 2002;Rauch et al, 2005;D'Angelo et al, 2007;Jalali et al, 2008;Fernández et al, 2009;Yu et al, 2011;Verhagen et al, 2012;Zhao et al, 2013;Rump et al, 2014; and this study. * Includes cases of Racedo et al, 2015 who only examined cardiac features of 25 individuals.…”
Section: Central Deletions (B-d C-d)supporting
confidence: 55%
“…Patient 3 of Jalali et al [2008] had a conotruncal heart defect, but it is not noted whether patient 4 (the parent of patient 3) has the same defect. Zhao et al [2013] reported on a cohort specifically with cardiac defects, and identified a single individual with a central deletion, but the types of cardiac defects are not specified. In Racedo et al [2015], 8/20 B-D deletion subjects and 1/5 C-D deletion subjects had cardiac defects.…”
Section: Central Deletions (B-d C-d)mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 105 patients with varying types of CHD performed by Erdogan et al [31] found de novo pathogenic CNVs in 3 % of their patients with isolated CHD. Zhao et al [49] examined CNVs in 100 Han Chinese adults with simple-to moderate-isolated CHD. They found large, rare CNVs in 39 % of their patients, compared with 21 % of the control group.…”
Section: Isolated Congenital Heart Defectsmentioning
confidence: 99%
“…Так, встановили значущу кореляцію між трьома поліморфізмами гена NFATс1 (rs7240256, rs11665469, rs754505) і виникненням дефек-ту міжшлуночкової перетинки (ДМШП) серця в однієї китайської популяції [15]. [16,17].…”
Section: п атол о г I я п атол о г I я огляди / Reviewsunclassified